Identification of hemocyanin as a novel non-cross-reactive allergen from the giant freshwater shrimp Macrobrachium rosenbergii - Surapon Piboonpocanun (2018)
Scope: Sensitization to giant freshwater shrimp Macrobrachium rosenbergii (Mr) was recently reported. However, the allergens have yet to be identified. This study aimed to identify and characterize a novel allergen of Mr shrimp. Methods and results: Extracted proteins were separated and purified by anion and in some experiments, size-exclusion chromatography. Serum IgE from shrimp allergic donors identified a candidate protein, which was characterized by LC-MS/MS. The specificity of IgE binding was tested using immunoblotting and inhibition ELISA. The IgE-binding profiles from 12 of 13 Mr allergic subjects that were pre-incubated with an extract of Penaeus monodon showed residual binding to ∼60-80kDa proteins. The 60-80kDa IgE-bound proteins were fractionated in the flow-through of anion chromatography showing a high IgE reactivity. Peptides identified by LC-MS/MS showed the proteins closely match subunits of hemocyanin (Hcs). Purified Hcs from hemolymph markedly inhibited binding of IgE from sera of Mr allergic subjects to solid-phased Mr proteins in inhibition ELISA. Conclusion: Hcs were identified as heat-stable, non-cross-reactive, high-molecular-weight (MW) allergens from Mr shrimp. Since circulatory organs are not always removed during food preparation, high concentrations of Hcs may be present along with shrimp meat, which contains the known cross-reactive tropomyosin protein. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.